ELECTRONIC ARCHIVE LEARNING MEDIA BASED ON PHPRAD ON DIGITAL ARCHIVING MATERIAL - Trina, Alya Sheva; Faslah, Roni; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This research aims to develop and test the feasibility of a PHPRAD-based Electronic Archive learning media to improve digital archiving skills at SMK Negeri 44 Jakarta. This study employs a Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data for this research were collected through validation by two material experts and two media experts, as well as response questionnaires from 32 students following a field trial. The data analysis technique used in this study combines descriptive quantitative and qualitative analysis. The results showed that the feasibility test yielded a score of 96.67% from material experts, 76.66% from media experts, and 87.84% from student responses, resulting in an overall average feasibility score of 87.06%, which is categorized as “Very Suitable.” Based on these results, the Electronic Archive learning media is deemed highly feasible and suitable as an alternative learning tool for the Digital Archiving material at SMK Negeri 44 Jakarta. This learning media effectively bridges the gap in digital archiving education by providing an innovative teaching tool. Furthermore, it also supports the mastery of practical skills relevant to the demands of the workforce, making it a highly recommended solution for optimizing the learning process at SMK Negeri 44 Jakarta.